Fitness maximization by dispersal: evidence from an invasion experiment. Issue 11 (1st November 2014) - Bonte, D.; De Roissart, A.; Wybouw, N.; Van Leeuwen, T.
Abstract : Dispersal is essential for population persistence in transient environments. While costs of dispersal are ubiquitous, individual advantages of dispersal remain poorly understood. Not all individuals from a population disperse, and individual heterogeneity in costs and benefits of dispersal underlie phenotype‐dependent dispersal strategies. Dispersing phenotypes are always expected to maximize their fitness by adaptive decision making relative to the alternative strategy of remaining philopatric. While this first principle is well acknowledged in theoretical ecology, empirical verification is extremely difficult, due to a plethora of experimental constraints. We studied fitness prospects of dispersal in a game theoretical context using the two‐spotted spider mite Tetranychus urticae as a model species. We demonstrate that dispersing phenotypes represent those individuals able to maximize their fitness in a novel, less populated environment reached after dispersal. In contrast to philopatric phenotypes, successful dispersers performed better in a low density post‐dispersal context, but worse in a high density philopatric context. They increased fitness about 450% relative to the strategy of remaining philopatric. The optimization of phenotype‐dependent dispersal, thus, maximizes fitness.